THE ROLE OF PERCEIVED USEFULNESS IN ATTITUDE TOWARD USING GOPAY LATER AMONG GENERATION Z IN YOGYAKARTA - Kristiana, Sekar Ayu; Prasetyo, Tri Utomo (International Economics and Business Proceedings, 2024)
This study analyzed the influence of Perceived Ease of Use (PEU) and Perceived Usefulness as mediating a variable on Attitude Toward Using (ATU) GoPay Later among Generation Z in Yogyakarta. The sampling method is carried out using the Non-Probability Sampling method with the Purposive Sampling technique. A total of 85 Generation Z (aged 18-27 years old) who lived in Yogyakarta and have made a transaction using GoPay Later at least once in the past year completed the questionnaire and became the participants of this study. To answer the research questions, SEM-PLS was applied using SmartPLS Ver. 3 Software. The Theory used in this study is the Theory of Technology Acceptance Models (TAM) developed by Davis (1989). This theory states that Attitude Toward Using a technology is influenced by Perceived Ease of Use and Percieved Usefulness. The result showed that Perceived Ease of Use does not have a significant direct effect on Attitude Toward Using. However, Perceived Ease of Use has a positive and significant direct effect on Perceived Usefulness. Perceived Usefulness has a positive and significant direct effect on Attitude Toward Using. These results indicated that Perceived Usefulness acted as a full mediator of the influence of Perceived Ease of Use on Attitude Toward Using. GoPay Later customers in this study did not consider the ease of use of the application, their attitude toward using GoPay Later was mainly affected by the usefulness of the application. This study contributes to BNPL companies that they should pay attention to the usefulness of the application.